The market presence of cooperative banks and stability in European banking: New evidence - Hans Groeneveld (Annals of Public and Cooperative Economics, 2026)
Abstract Most studies examining differences between cooperative banks (CBs) and other banking institutions rely on bank‐level data, thereby overlooking effects of the market presence of CBs on banking market structures. To address this gap, we test whether CB's domestic market share predicts national banking stability ( Z ‐scores) using a unique panel dataset for 15 European countries spanning 1991–2024 and a two‐way fixed‐effects framework. Our empirical findings confirm that CBs contribute to overall banking stability through a direct channel, reflecting their own stability characteristics, and an indirect channel, reflecting their influence on the behaviour and risk‐taking of other banks. In some model specifications, we find evidence of a non‐linear relationship, suggesting that the contribution of CBs to banking stability becomes positive only after their market share surpasses a critical threshold. The policy implications are that the stabilizing role of CBs within national banking systems should be adequately recognized in the design and implementation of banking regulation and supervision. It would be welfare reducing if smaller CBs were to disappear because they may not be able to afford the ever‐increasing compliance costs in the future. This would put downward pressure on the stability and diversity of the entire banking sector.